2003
DOI: 10.1007/s00216-003-2220-7
|View full text |Cite
|
Sign up to set email alerts
|

Determination of decabromodiphenyl ether in sediments using selective pressurized liquid extraction followed by GC–NCI-MS

Abstract: A method based on selective pressurized liquid extraction (SPLE) followed by gas chromatography-negative ion chemical ionization-mass spectrometry (GC-NCI-MS) has been evaluated for analysis of decabromodiphenyl ether (PBDE-209) in sediment samples. Instrumental operating conditions such as source temperature and system pressure were optimized in the NCI-MS system, giving an instrumental detection limit of 2 pg. The limit of determination of the entire SPLE-GC-NCI-MS procedure was around 50 pg g(-1) dry weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 16 publications
(18 reference statements)
1
21
1
Order By: Relevance
“…BFRs concentrations in this study were lower than other similar studies in other countries [22][23][24][25][27][28][29][30], however the characteristics of the landfill like the great volume of solid wastes as well as the re injection of leachates into the landfill could contribute to the release and concentration of contaminants in the landfill. …”
Section: Resultscontrasting
confidence: 84%
“…BFRs concentrations in this study were lower than other similar studies in other countries [22][23][24][25][27][28][29][30], however the characteristics of the landfill like the great volume of solid wastes as well as the re injection of leachates into the landfill could contribute to the release and concentration of contaminants in the landfill. …”
Section: Resultscontrasting
confidence: 84%
“…Some reports reveal BDE-209 and BDE-47 are the dominant congeners in most cases of the abiotic and the biotic, respectively. For example, the BDE-209 concentration is 12 lg/l in water, over 100 lg/kg in effluent particulates of water (La Guardia et al, 2004), 248 ± 81 lg/kg in sewage sludge (Christensen et al, 2003), and 0.5-132 lg/kg in sediments (Eljarrat et al, 2004;Sawal et al, 2004). It was reported that BDE-47 predominated about 50% or more of the total PBDEs in fish species from North America, the European Union and China (Hites, 2004;Xiang et al, 2007;Xian et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The column was eluted with hexane followed by n-hexane:DCM (1:1) to separate PCBs from most PBDEs except BDE 47 which partially eluted in Fraction 1. The second elution of 15% DCM/n-hexane contained the PBDEs except for BDE 209 which was not recovered efficiently from Florisil (31). Samples from Alaska and Svalbard were chromatographed on activated silica gel (8 g, 1.1 cm i.d.…”
Section: Methodsmentioning
confidence: 99%